Community capacity building for tourism in a heritage village: the case of Hawraman Takht in Iran - Ghaderi, Zahed; Abooali, Gelareh; Henderson, Joan (Routledge, 2017)
This paper is concerned with the concept and practice of community capacity building (CCB) within the context of rural tourism.Issues are discussed with specific reference to an Iranian village which is a popular visitor destination. The results of interviews conducted with 34 stakeholders reveal a strong interest in tourism, yet an absence of CCB initiatives due to a variety of factors which include a lack of official support.It appears that CCB is not a prerequisite for tourism at a local level, but respondents felt that it could assist in maximising opportunities for communities to benefit from such development. The study enhances knowledge and understanding of the meaning and implementation of CCB in a part of the world which has been relatively neglected in the literature. Results also have implications for authorities and the tourism industry at work in rural areas as well as residents. © 2017 Informa UK Limited, trading as Taylor & Francis Group